Application of accuracy control system in Batam shipyard - Andalas, Ronny (2005)
Accuracy Control System (ACS) in shipbuilding industries is proven to have reduced production time, rework, and improved productivity and finally achieved quality ofproduct. This concept had been implemented in many shipyards worldwide especially in Japan, USA and Europe. With the recent shipbuilding development in Batam region, with the emergence of more than forty shipyards, the application of ACS could brought a significant impact to the well being and competitiveness at aatam shipyards. Therefore, this research study is carried out to determine the status of the level ofACS implementation in Batam shipyards, hence proposed for suitable improvement or implementation wherever necessary. This research started with two different surveys; first survey conducted at fourteen shipyards by using questionnaire in order to determine the present status of ACS application. The second survey was conducted on a specific shipyard, Le. PT. Pan-United Shipyard in order to determine the present quality system employed. A pilot study on the initial implementation of ACS has also been carried out in this shipyard. A stem block (block 1) of a ongoing project (Hul1163) has been selected for the study and the measurement was taken and recorded systematically. Based on these measurements, several analysis have heen performed which lead to the conclusion that the percentage of rework, production time and production cost can be reduced significantly with the ACS implementation. Based on these findings, a proposal was then recommended to the shipyards on how ACS can be initiated. It is hope that with this recommendation, the quality of ship produced can be improved, hence reduces production cost and increase competitiveness.